The stimulation of sense of community on the early childhood’ online learning - Sukmadewi, A. A Putu Eka; Tirtayani, Luh Ayu (Universitas Pendidikan Ganesha, 2021)
The change of conventional learning into online learning process due to COVID-19 pandemic had brought a significant change towards sense of community stimulation. Direct learning activities are needed considering that the early childhood education progress emphasize sense experiences in which a direct interaction between teachers and students. A dynamic interaction could improve roles as a part of society (sense of community). It was designed in the form of descriptive quantitative to find out a clear picture about the sense of community stimulation conducted by the teachers of The Early Childhood Education Program in North Denpasar, Bali. Proportional random sampling was used to choose the participants. Questionnaire was the instruments used in this study in which it was spread by using Google Form. The data were analysed quantitatively by using statistical descriptive in the percentage form. The findings showed that sense of community stimulation done by the early childhood teachers was positive in the percentage of 85,94 %. The other results were viewed from four indicators such as; teachers’ knowledge categorized as positive (79,59%), the sense of community stimulation strategy in the positive category categorized in strongly positive (86,52%), the sense of community stimulation’s planning, strategy categorized into strongly positive, and the collaboration and enrichment were strongly positive (92,16%).